Contribution of Teacher Compensation and Teacher Commitment to State Elementary School Teacher Performance In The District of Batang Cenaku Indragiri Hulu District - Setiawan, Andik; Rusdinal, Rusdinal; Yahya, Yahya (International Journal for Educational and Vocational Studies, 2020)
The purpose of this study is to find out and explain: 1) The contribution of school principal compensation to teacher performance. 2) The contribution of teacher commitment to teacher performance. 3) Contribution of school principal compensation and teacher commitment together to teacher performance in the SDN Batang Cenaku District. This type of research is a correlational quantitative study. The population in this study were all elementary school teachers who had become Civil Servants in Cenaku Subdistrict, Indragiri Hulu Regency, which numbered 110 people. The sample of this research was taken using stratified proportional random sampling technique, The sample of this study was 93 people. Data collection techniques in this study used for data collection were questionnaires. Data analysis using correlation and regression techniques. Based on the results of the analysis it can be concluded as follows: 1) Compensation contributes to the performance of elementary school teachers with a contribution rate of 10.5%, this means that compensation contributes to teacher performance. 2) Commitment contributes to the performance of elementary school teachers with a magnitude of 9.4%. Thus, a significant commitment to teacher performance. This means that the better the commitment, the better the teacher's performance in carrying out their duties, and vice versa. 3) Compensation and commitment together contribute to teacher performance by 18.5%. This explains that to improve good and ideal teacher performance should be done through increased compensation and commitment.